Cost analysis of large-scale implementation of the 'Helping Babies Breathe' newborn resuscitation-training program in Tanzania. Issue 1 (December 2016) - Chaudhury, Sumona; Arlington, Lauren; Brenan, Shelby; Kairuki, Allan; Meda, Amunga; Isangula, Kahabi; Mponzi, Victor; Bishanga, Dunstan; Thomas, Erica; Msemo, Georgina; Azayo, Mary; Molinier, Alice; et al.
Abstract Background Helping Babies Breathe (HBB) has become the gold standard globally for training birth-attendants in neonatal resuscitation in low-resource settings in efforts to reduce early newborn asphyxia and mortality. The purpose of this study was to do a first-ever activity-based cost-analysis of at-scale HBB program implementation and initial follow-up in a large region of Tanzania and evaluate costs of national scale-up as one component of a multi-method external evaluation of the implementation of HBB at scale in Tanzania. Methods We used activity-based costing to examine budget expense data during the two-month implementation and follow-up of HBB in one of the target regions. Activity-cost centers included administrative, initial training (including resuscitation equipment), and follow-up training expenses. Sensitivity analysis was utilized to project cost scenarios incurred to achieve countrywide expansion of the program across all mainland regions of Tanzania and to model costs of program maintenance over one and five years following initiation. Results Total costs for the Mbeya Region were $202, 240, with the highest proportion due to initial training and equipment (45.2%), followed by central program administration (37.2%), and follow-up visits (17.6%). Within Mbeya, 49 training sessions were undertaken, involving the training of 1, 341 health providers from 336 health facilities in eight districts. To similarly expand the HBB program across the 25 regions of mainland Tanzania, the total economic cost is projected to be around $4, 000, 000 (around $600 per facility). Following sensitivity analyses, the estimated total for all Tanzania initial rollout lies between $2, 934, 793 to $4, 309, 595. In order to maintain the program nationally under the current model, it is estimated it would cost $2, 019, 115 for a further one year and $5, 640, 794 for a further five years of ongoing program support. Conclusion HBB implementation is a relatively low-cost intervention with potential for high impact on perinatal mortality in resource-poor settings. It is shown here that nationwide expansion of this program across the range of health provision levels and regions of Tanzania would be feasible. This study provides policymakers and investors with the relevant cost-estimation for national rollout of this potentially neonatal life-saving intervention.